Retrato de un grupo de líderes sindicales (2022)
Aparecen de pie de izquierda a derecha: Eliseo Hernández, Ernesto Barata, L. Santacoloma, Manuel de J. Romero, Ignacio Torres Giraldo, Erasmo Valencia y Neftalí Arce. Sentados en el mismo orden: Raúl Eduardo Mahecha, Sofía López, María Cano y Juan de Dios Romero